Feasibility, acceptability and cost efficiency of using webinars to deliver first‐line patient education for people with Irritable Bowel Syndrome as part of a dietetic‐led gastroenterology service in primary care. Issue 6 (20th August 2020) - Williams, M.; Barclay, Y.; Harper, L.; Marchant, C.; Seamark, L.; Hickson, M.
Abstract: Background: Irritable bowel syndrome (IBS) is a chronic functional gastrointestinal disorder. International research suggests dietary intervention as a first‐line approach, although dietetic services are struggling to cope with demand. Digital technology may offer a solution to deliver appropriate patient education. The present study aimed to assess the feasibility, acceptability and cost efficiency of using webinars to deliver first‐line IBS advice to patients as part of a dietetic‐led gastroenterology service in primary care. Methods: Patients were directed to an IBS First Line Advice webinar on a specialist NHS website. Data were collected from patients pre‐ and post‐webinar use using an online survey. Results: In total, 1171 attendees completed the pre‐webinar survey and 443 completed the post‐webinar survey. Attendees ranged from under 17 years to over 75 years. Of the attendees, 95% found the webinar easy to access and 91% were satisfied with the content of the webinar. Those with excellent or good knowledge rose from 25% pre‐webinar to 67% post‐webinar, and confidence in managing their condition improved for 74% of attendees. Using the webinars led to a 44% reduction in referrals for one‐to‐one appointments with a specialist dietitian in the first year of use. The value of the clinical time saved is estimated at £3593 per annum. The one‐off cost of creating the webinar was £3597. Conclusions: The use of webinars is a feasible, acceptable and cost‐efficient way of delivering first‐line patient education to people suffering with Irritable Bowel Syndrome as part of a dietetic‐led gastroenterology service in primary care. Abstract : Using irritable bowel syndrome (IBS) patient education webinars led to a 44% reduction in referrals for one‐to‐one appointments with a specialist dietitian in the first year of use. The use of webinars was a feasible, acceptable and cost‐efficient way of delivering first‐line patient education to people suffering with IBS as part of a dietetic‐led gastroenterology service in primary care. A reduction in referrals through the use of webinars could significantly contribute to the release of clinical time in a wide range of clinical areas, while the money saved could lead to effective reallocation of clinical funding at a national level which reflects the aims of the 2019 NHS Long Term Plan.